CONSTRUCTIONS OF IDENTITY (VIII) DISCOURSES IN THE ENGLISH‐SPEAKING WORLD - PRECUP, Amelia; PETRAR, Petronia (Presa Universitară Clujeană, 2017)
The discourses on identity in the era of post-modernity, post-colonialism, and possibly post-nation state, have taken on greater significance. This discussion, however, raises some essential theoretical questions, such as: ‘Is one’s identity, in the present, a stable state of being or a descent below construction processes?’. Moreover, David Hollinger (44) poses a key question about communal, ethnic and identity formation in the U.S.: “Who decides what your identity is?”, a question that proves instrumental in a discussion on identity politics and identity ascription.